THE USE OF MEDICINES IN TREATING HYPERTENSION IN DEPARTMENT OF CARDIOLOGY AT CAN THO CENTRAL GENERAL HOSPITAL - Pham , Thai Tran; Duong, Xuan Chu; Dang, Duy Khanh (Cantho Journal of Medicine and Pharmacy, 2026)
Background: Hypertension is one of main factors of heart diseases and its ratio is increasing day by day. Controlling the target blood pressure will reduce the mortality rate and also injured organs. Objectives: (1) Determining the using features of medicines in treating hypertension. (2) Discovering the ratio of patients obtain the target blood pressure. Materials and methods: Using a cross-sectional study was conducted among 343 medical records of patients who were diagnosed of hypertension from January 2019 to December 2019 at Department of Cardiology of Can Tho Central General Hospital. Samples were selected by systematic random sampling method, the information were collected from medical records and survey forms. Results: All antihypertensive drugs in this research belonged to the antihypertensive list recommend by Ministry of Health and Vietnam National Heart Association. Calcium channel blockers (CCBs) and Angiotensine II receptor blockers (ARBs) were the two most popular drug categories (42.6% and 39.1%, respectively). The rate of using multi-therapy regimens was higher than the rate of using uni-therapy (59.8% and 40.2%). The rate of patients obtaining the target blood pressure before leaving the hospital was 94.8%. Conclusions: All antihypertensive drugs in this research belonged to the antihypertensive list recommend by Ministry of Health and Vietnam National Heart Association. The rate of using multi-therapy regimens was higher than the rate of using unitherapy. Most patients had the target blood pressure before being discharged from hospital.